2017
DOI: 10.1007/s12560-017-9287-3
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance of Human Bocaviruses in Urban Sewage in Greater Cairo, Egypt

Abstract: Human bocavirus (HBoV) is predominantly found in the respiratory tract infections and in the stool of patients with gastroenteritis symptoms. However, data on the prevalence of HBoV genotypes in environmental samples are limited. Here we addressed the prevalence of HBoV in sewage collected from three different wastewater treatment plants in Egypt. HBoV-1, HBoV-2, and HBoV-3 were detected, whereas none of the samples were positive for HBoV-4. The median concentration of HBoV in influent samples was 8.5 × 10 GC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
3
23
1
Order By: Relevance
“…However, increasing data suggest a role for this virus, at least for HBoV-2, as an etiological agent of gastroenteritis in the pediatric population (25). HBoV can be discharged in untreated wastewaters through virus shedding and, consequently, disperse throughout water environments, as shown recently in Italy (30,31) and elsewhere (26,28,32). Bivalve mollusks concentrate several human pathogens transmitted by the fecal-oral route, including a wide range of enteric viruses (35)(36)(37), whose presence in these aquatic organisms may be evaluated to assess the safety of the product for human consumption (38) or for biomonitoring purposes (39,40).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, increasing data suggest a role for this virus, at least for HBoV-2, as an etiological agent of gastroenteritis in the pediatric population (25). HBoV can be discharged in untreated wastewaters through virus shedding and, consequently, disperse throughout water environments, as shown recently in Italy (30,31) and elsewhere (26,28,32). Bivalve mollusks concentrate several human pathogens transmitted by the fecal-oral route, including a wide range of enteric viruses (35)(36)(37), whose presence in these aquatic organisms may be evaluated to assess the safety of the product for human consumption (38) or for biomonitoring purposes (39,40).…”
Section: Resultsmentioning
confidence: 98%
“…Recently, the presence of HBoV in environmental samples, including wastewaters, sewage sludge, and water impacted by sewage, has also been reported (26)(27)(28)(29)(30)(31)(32)(33), therefore suggesting a potential role of water in the transmission of this virus. To date, no information on the presence of HBoV in food matrices is available.…”
mentioning
confidence: 97%
“…There are currently limited data worldwide exploring the circulation of HBoV from environmental samples. Some studies have detected human bocavirus in river water [25,26] and wastewater samples [27][28][29]. Even though the role of HBoV in gastrointestinal infections is not fully understood, the risk of infection via contaminated water should be taken into consideration since many rural communities still face challenges of poor sanitation and hygiene practices [15].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently limited data worldwide exploring the circulation of HBoV from environmental samples. Some studies have shown the prevalence of Human Bocavirus in river water (22,23) and wastewater samples (24)(25)(26). Even though the role of HBoV in gastrointestinal infections still remains to be not fully understood, the risk of infection via contaminated water should be taken into consideration since many rural communities still face challenges of poor sanitation and hygiene practices (11).…”
Section: Discussionmentioning
confidence: 99%